Online-Based Distance Learning During Covid-19 Pandemic at Primary School - Tenika Illananingtyas (eL Bidayah: Journal of Islamic Elementary Education, 2021)
The Indonesian government is currently facing a Covid-19 pandemic that is still beyond its control. From print media to electronic media, the mass media continues to report on the number of victims infected with this virus, and the number is declining. One of the predictive steps to prevent the spread of this virus is to maintain social distancing. As a formal educational institution, the school responded quickly to this situation. The school does not hope that by changing the face-to-face learning mode, the virus will spread in its environment. I.e. through distance learning or online learning (online). Therefore, this is the task of the teacher, that is, to be able to create various activities in online learning that can attract students' interest in learning. Especially learning English requires not only theory, but also a lot of practice. Therefore, interactive learning in the form of activities is required to allow students to actively participate in the online learning process. This research aims to obtain important information about the effectiveness of online distance learning (PJJ) for primary schools in Kediri City. The research methods used descriptive qualitative methods to 20 respondents. According to the analysis data, the research results show that online distance learning for elementary schools is considered to be quite effective. [Pemerintah Indonesia saat ini sedang menghadapi pandemi Covid-19 yang masih di luar kendali. Dari media cetak hingga media elektronik, media massa terus memberitakan jumlah korban yang terinfeksi virus ini, dan jumlahnya terus menurun. Salah satu langkah prediktif untuk mencegah penyebaran virus ini adalah dengan menjaga jarak sosial. Sebagai lembaga pendidikan formal, sekolah merespon dengan cepat situasi ini. Pihak sekolah tidak berharap dengan mengubah mode pembelajaran tatap muka, virus akan menyebar di lingkungannya, yaitu dengan melalui pembelajaran jarak jauh atau pembelajaran online. Oleh karena itu, inilah tugas guru yaitu mampu menciptakan berbagai aktivitas dalam pembelajaran online yang dapat menarik minat siswa untuk belajar. Apalagi belajar bahasa Inggris tidak hanya membutuhkan teori, tetapi juga banyak latihan. Oleh karena itu, pembelajaran interaktif dalam bentuk kegiatan diperlukan agar siswa dapat berpartisipasi aktif dalam proses pembelajaran online. Penelitian ini bertujuan untuk memperoleh informasi penting tentang efektivitas pembelajaran jarak jauh (PJJ) online untuk sekolah dasar di wilayah Kota Kediri. Metode penelitian yang digunakan adalah metode deskriptif kualitatif terhadap 20 responden. Berdasarkan data analisis, hasil penelitian menunjukkan bahwa PJJ online untuk SD dinilai cukup efektif]